2020
DOI: 10.1007/s10453-020-09629-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atmospheric circulation conditions on Betula and Alnus pollen concentrations in Wrocław, Poland

Abstract: The influence of atmospheric circulation conditions on pollen concentrations of two taxons (Betula and Alnus) in Wroclaw, Poland, for the years 2005-2014 was analysed. Pollen concentration was analysed separately for twenty circulation types that were determined using objective classification. The results indicate the atmospheric circulation conditions favourable for both low and high pollen concentrations over Central Europe. Pollen concentrations vary significantly according to circulation types. The highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In terms of evaluation of the results from the circulation perspective, the classification of atmospheric circulation developed by H. Ojrzyńska [66][67][68] was used. This classification was carried out for the region of the Sudety Mountains and their surroundings, including southwest Poland, southeast Germany, and east Czechia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of evaluation of the results from the circulation perspective, the classification of atmospheric circulation developed by H. Ojrzyńska [66][67][68] was used. This classification was carried out for the region of the Sudety Mountains and their surroundings, including southwest Poland, southeast Germany, and east Czechia.…”
Section: Methodsmentioning
confidence: 99%
“…Using the spline function, the data were interpolated to a spatial resolution of 5 km × 5 km. To determine the circulation type for each day, a prevailing type was calculated by applying the mode function for all the 5 km × 5 km grid cells [67]. The direction of advection was evaluated based on the wind direction from the 700 hPa isobaric level for a wind speed higher than 2 m/s.…”
Section: Methodsmentioning
confidence: 99%
“…Grundstro ¨m et al (2017) concluded that the approach based on types of weather is a relatively easy method for characterizing weather conditions on a synoptic scale; it groups many meteorological variables relevant to the processes deciding on high or low concentration levels of pollen. Studies conducted in Go ¨teborg and Malmo ¨showed that high concentrations of birch pollen were correlated with dry and moderately calm conditions during an anti-cyclone and types of weather with geostrophic NE, SE, and S winds, and the lowest concentration levels were found in humid and windy conditions with wind directions SW, W, and NW, as well as for a cyclonic type (Grundstro ¨m et al, 2017). Ojrzyn ´ska et al (2020 noted that the highest pollen concentration for both alder and birch in Wrocław (Poland) is observed during warm, sunny, and dry anti-cyclonic circulations an anti-cyclone in the lower and upper troposphere, especially for the types with advection from the SW direction.…”
Section: Discussionmentioning
confidence: 95%
“…The results of the analysis on CTIS were presented as a calendar of weather conditions for particular 10-day periods. In order to present the most intensive heat-stress conditions and their relation to the atmospheric circulation, a calendar of circulation types developed by H. Ojrzyńska was used [85][86][87]. This classification concerns the Sudetes Mountains and the surrounding regions, and is based on the data related to vorticity (C, cyclonic; A, anticyclonic) and the direction of advection: NE, northeast (1-90 • ); SE, southeast (91-180 • ); SW, southwest (181-270 • ); NW, northwest (271-360 • ); and XX, indeterminate direction.…”
Section: Methodsmentioning
confidence: 99%
“…These data were interpolated to a spatial resolution of 5 km × 5 km using the spline function. Circulation types for particular days were assessed based on the prevailing type, which was calculated by applying the mode function for all the 5 km × 5 km grid cells [86]. The types of vorticity were evaluated using geopotential values from the 850 hPa isobaric level.…”
Section: Methodsmentioning
confidence: 99%